A DESIGN OF GRAMMAR TEACHING VIDEO BY USING VIDEOSCRIBE - Muaffi Alif; Urai Salam; Zainal Arifin (Universitas Tanjungpura, 2019)
AbstractThis study aimed to design a grammar teaching video by using animated video made from videoscribe to Junior High School students. This research was a development research. Eighth grade students of SMP Negeri 16 Pontianak were subjects of this study. This research utilized a questionnaire in google form as the instrument of data collection to gain the needs of students. According to the result of questionnaire, most of students preferred to learn English by using a video in the classroom. The researcher designed an animated grammar teaching video and the topic was superlative adjectives. The video could be advantageous for students since the animated video delightfully attracts the attention of students in the classroom. The teacher could make use of the animated grammar teaching video as a medium in teaching English. The difficulties in teaching English grammar might be decreased when applying animated grammar teaching video, and the teacher could design her own animated video by using the videoscibe in the further. Keywords: English Grammar, Grammar Teaching Video, Videoscribe